Pegylated liposomal doxorubicin and mitomycin C in combination with infusional 5-fluorouracil and sodium folinic acid in the treatment of advanced gastric cancer: results of a phase II trial - Gnad-Vogt, Ulrike; Hofheinz, Ralf-Dieter; Saußele, Susanne; Kreil, Sebastian; Willer, Andreas; Willeke, Frank; Pilz, Lothar R.; Hehlmann, Rüdiger; Hochhaus, Andreas (Anti-cancer drugs, 2005)
Mitomycin C (MMC) in combination with infusional 5-fluorouracil (5-FU) is a well-tolerated active combination therapy for advanced gastric cancer. Pegylated liposomal doxorubicin (Caelyx) has been combined with this regimen in a phase I study exhibiting promising activity in patients with upper gastrointestinal tumors. In the present study, we investigated activity and tolerability of this three-drug regimen in patients with gastric cancer. Patients with advanced or metastatic gastric cancer were recruited to receive weekly infusional 5-FU (2000 mg/m2) mixed with sodium folinic acid (FA; 500 mg/m2) in one pump (days 1, 8, 15, 22, 29, 36). On days 1 and 29, Caelyx (20 mg/m2) was given as a 1-h, and MMC (7 mg/m2) was applied as bolus injection on days 8 and 36. Treatment courses were repeated on day 57. Twenty-seven patients with a median age of 66 years were recruited in a single center; 56% had histologically proven peritoneal carcinomatosis and 26 patients are evaluable for toxicity. Common Toxicity Criteria of the National Cancer Institute grade 3 toxicity was recorded in 34% of the patients (anemia 12%, leukocytopenia 8%, febrile neutropenia 4%, thrombocytopenia 12%, nausea 15%, diarrhea 8% and mucositis 4%). One patient developed hemolytic-uremic syndrome. One complete (5%) and eight partial responses (42%) were observed in 19 patients evaluable for response according to WHO criteria. Seven patients had no change (37%) and three (16%) progressive disease. Six patients with peritoneal carcinomatosis not amenable to WHO response assessment had progression-free intervals between 8 and 21 months. Median survival for all patients was 14.7 months and median time to progression was 8.4 months. We conclude that this new three-drug combination regimen yields a promising overall response rate (47%) in patients with gastric cancer despite the inclusion of a majority of elderly patients at moderate or high risk of death in this trial. Its safety and good tolerability as established in the phase I trial was confirmed.